Pengaruh CAR, FDR dan BOPO terhadap NPF di BCA Syariah Periode 2013 - 2022 - Yasni Gustini; Ima Amaliah (Bandung Conference Series: Economics Studies, 2024)
Abstract. NPF (Non-Performing Financing) is a ratio of non-performing financing that shows the proportion of non-performing financing to total financing disbursed by Islamic banking. The aspects that cause non-performing financing can be factors from the bank, customers, and parties outside the bank. The aspects that come from the bank are Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), and Operating Costs to Operating Income (BOPO). Based on this phenomenon, the problems in this study are formulated as follows: (1) Is there a relationship between CAR to NPF? (2) Is there a relationship between FDR to NPF? (3) Is there a relationship between BOPO to NPF. Researchers used a descriptive analysis technique method using a quantitative approach. The population selected in this study was BCA Syariah in 2013-2022. With the sampling technique, namely Purposive Sampling obtained from the annual report of BCA Syariah. The data collection techniques used in this research are documentation and literature study. The data analysis technique used in this research is the Rank Spearman correlation analysis technique. The results of this study are: There is a positive relationship between CAR and BOPO to NPF with non-performing financing which is in the strong/high category and between FDR to NPF with non-performing financing which is in the low category. Abstrak. NPF (Non-Performing Financing) merupakan rasio pembiayaan bermasalah yang menunjukkan proporsi pembiayaan bermasalah terhadap total pembiayaan yang disalurkan oleh perbankan syariah. Aspek-aspek yang menyebabkan terjadinya pembiayaan bermasalah bisa faktor dari bank, nasabah, dan pihak diluar bank. Adapun aspek yang berasal dari bank adalah Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), dan Biaya Operasional terhadap Pendapatan Operasional (BOPO). Berdasarkan fenomena tersebut, maka permasalahan dalam penelitian ini dirumuskan sebagai berikut: (1) Apakah terdapat hubungan antara CAR terhadap NPF? (2) Apakah terdapat hubungan antara FDR terhadap NPF? (3) Apakah terdapat hubungan antara BOPO terhadap NPF?. Peneliti menggunakan metode teknik analisis deskriptif dengan menggunakan pendekatan kuantitatif. Populasi yang dipilih dalam penelitian ini adalah BCA Syariah tahun 2013-2022. Dengan teknik pengambilan sampel yaitu Purposive Sampling diperoleh dari laporan tahunan BCA Syariah. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah dokumentasi dan studi pustaka. Adapun teknik analisis data yang digunakan dalam penelitian ini adalah teknis analisis korelasi Rank Spearman. Hasil dari penelitian ini adalah: Terdapat hubungan positif antara CAR dan BOPO terhadap NPF dengan pembiayaan bermasalah yang termasuk kategori kuat/tinggi dan antara FDR terhadap NPF dengan pembiayaan bermasalah yang termasuk kategori rendah.